Students' Collaborative Learning Attitudes and Their Satisfaction with Online Collaborative Case-Based Courses. Issue 4 (2nd October 2018) - Wengrowicz, Niva; Swart, William; Paul, Ravi; Macleod, Kenneth; Dori, Dov; Dori, Yehudit Judy
ABSTRACT: Case-based learning is an interactive group learning approach that embodies the principles of Socratic inquiry. It is a common pedagogy used in many disciplines including business, law, and health. With online learning being the fastest growing segment of higher education, case-based learning is also finding its way into online courses. This research was conducted on a population of 698 students enrolled in online case-based courses. The use of Structural Equation Modelling provided an understanding of the factors that influence student satisfaction. Through Logistics Regression, the extent to which these factors do influence satisfaction was determined. The findings indicate that the greatest predictors of student satisfaction were the interaction and understanding between the students and the instructor. Furthermore, a student's pre-existing attitude toward interactive group learning is also a significant factor in predicting student satisfaction. The conclusions point to a lack of understanding by students on how to engage in effective interactive online group learning. The recommendation is that training in online collaborative skills be considered as a front-end to any online case-based course.